The Role of the Early Years Librarian in Developing an Information Community: a Case Study of Effective Partnerships and Early Years Literacy within a Sure Start Project in Wakefield - Rankin, Carolyn; Brock, Avril; Wotton, Carol; Halpin, Edward (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Sure Start is a UK government initiative addressing social exclusion in local communities through a multi-disciplinary team approach. The Early Years Librarian can be a significant team member in responding to child development and early years literacy. A case study of the Wakefield district investigates the role of the Early Years Librarians in responding to the government agenda. Partnership work and focusing of provision based on parental consultation are key issues. Le projet « Sure Start » est une initiative du gouvernement du Royaume-Uni abordant le problème de l’exclusion sociale dans les communautés locales, à travers l’approche d’une équipe multidisciplinaire. Les bibliothécaires « Early Years » peuvent jouer un rôle important dans le développement de l’enfant et dans la première phase de culture informationnelle. Une étude de cas dans la circonscription de Wakefield explore le rôle des bibliothécaires « Early Years » œuvrant pour le plan d’action du gouvernement. Le travail de partenariat et l’utilisation de dispositions basées sur la consultation parentale sont des questions-clés.